Evaluasi promosi perpustakaan terhadap pemanfaatan digital library Universitas Muhammadiyah Magelang - Widayati, Jamzanah Wahyu; Isnaini, Rizki Shofak (FPPTI Jawa Tengah, 2021)
ABSTRACT Library promotion aims to communicate the products owned by the library to the public. It is hoped that the public will be interested in utilizing these products in fulfilling the needs of information. This study evaluates the promotions that have been carried out by the library of Muhammadiyah University of Magelang (UNIMMA) by using descriptive qualitative methods. The result shows that the promotions have not reached all academicians, especially in utilizing the UNIMMA digital library. User education for new students and more interesting promotional content are required.